Case 3459: Allotypes should be from the type series: a position paper for reinstating Recommendation 72A from the third edition of the Code that defines the term ‘allotype’. - Santiago-Blay, Jorge A; Ratcliffe, Brett C; Krell, Frank-T; Anderson, Robert (Bulletin of Zoological Nomenclature)
Case not noticed (is an article, published BZN 65 (4): 260–264). Case closed BZN 75 (31 December 2018): 302